Imaging Protein Misfolding in the Brain Using β-Sheet Ligands - Harada, Ryuichi; Okamura, Nobuyuki; Furumoto, Shozo; Yanai, Kazuhiko (Frontiers in Neuroscience, 2018)
Neurodegenerative diseases characterized by pathological protein accumulation in cells are termed “proteinopathies.” Although various protein aggregates share cross-β-sheet structures, actual conformations vary among each type of protein deposit. Recent progress in the development of radiotracers for positron emission tomography (PET) has enabled the visualization of protein aggregates in living brains. Amyloid PET tracers have been developed, and are widely used for the diagnosis of Alzheimer’s disease and non-invasive assessment of amyloid burden in clinical trials of anti-dementia drugs. Furthermore, several tau PET tracers have been successfully developed and used in the clinical studies. However, recent studies have identified the presence of off-target binding of radiotracers in areas of tau deposition, suggesting that concomitant neuroinflammatory changes might affect tracer binding. In contrast to amyloid and tau PET, there are no established tracers for imaging Lewy bodies in the human brain. In this review, we describe lessons learned from the development of PET tracers and discuss the future direction of tracer development for protein misfolding diseases.